Analysis on characteristics and operation mode of direct solar collector coupled heat pump drying system. (April 2023) - Yao, Muchi; Li, Ming; Wang, Yunfeng; Li, Guoliang; Zhang, Ying; Gao, Meng; Deng, Zhihan; Xing, Tianyu; Zhang, Zude; Zhang, Wenxiang
Abstract: To solve the intermittent problem of solar drying systems, this study proposes a solar vacuum tube collector coupled heat pump drying (HPD) system that can adopt three operating modes as different climatic conditions. The performance of the system under different working modes and drying characteristics was analyzed; moreover, the system was also based on the relationship between energy supply and consumption. The results show that under load conditions, the system runs in the solar drying (SD) mode and the drying chamber temperature can reach >50 °C. In the HPD mode, the average heating power of the system is 11.88 kW, the heating coefficient is 2.26 and the average thermal efficiency of the heat exchanger is 39.3%. In the solar-assisted heat pump drying (SAHPD) mode, the average coefficient of performance of the system is 3.26, compared to HPD model, a 44.2% increase. The heating ratios of the SD, HPD and SAHPD modes were 37.9%, 58.5% and 3.6%, respectively. Furthermore, the Two-term models with R 2 value of 0.9986 and RMSE value of 0.01038 was considered the best drying kinetics model for the vacuum tube collector coupled heat pump drying grapes. This study guides the application of SAHPD systems in agricultural products drying.